A flow-through holed PDMS membrane as a reusable microarray spotter for biomedical assays. Issue 1 (31st October 2014) - Lamberti, A.; Angelini, A.; Ricciardi, S.; Frascella, F.
Abstract : A holed-designed PDMS membrane is proposed as an innovative microarray spotter exploiting a vacuum procedure and verifying a good level of reproducibility of spotting fluorescent proteins over large areas. Abstract : We propose the exploitation of a holed-designed poly(dimethyl)siloxane (PDMS) membrane as an innovative microarray spotter. The membrane is fabricated by a simple technological approach and can be reused several times. A good level of reproducibility is found upon spotting fluorescent proteins at different concentrations over large areas.